PERANCANGAN DAN IMPLEMENTASI SMART GARDEN BERBASIS INTERNET OF THINGS (IOT) PADA PERUMAHAN CENTRAL PARK CIKARANG - Ikhsan Romli; Kristoforus Lensiprimo Nong Hugo; Irfan Afriantoro (Indonesian Journal of Business Intelligence (IJUBI), 2021)
Technological developments, especially in agriculture and plantations in era 4.0, have greatly increased over time. One of them is in terms of plant care. Plant care is one of the activities carried out to keep plants fertile and healthy. Moreover, in the dry season plant care is very important to do such as, doing watering periodically in accordance with the right time, and also light lighting must be in accordance with the needs of the plant. In this writing, researchers designed a tool that can respond to and work on commands that have been sent, and also reply to messages about the information displayed on the blynk application. Smart Garden Tools It uses NodeMCU 8266 as a controller as well as a soil moisture sensor as a soil moisture detector, and DHT11 as a temperature and humidity sensor. The results of this study are to minimize the occurrence of damage to plants, make it easier for residents to control and monitor the condition of the house in real time, and also to improve the quality of plants in order to grow properly.